Molecular pathways in mitochondrial disorders due to a defective mitochondrial protein synthesis - Antolínez-Fernández, Álvaro; Esteban-Ramos, Paula; Fernández-Moreno, Miguel Ángel; Clemente, Paula (Frontiers in Cell and Developmental Biology, 2024)
Mitochondria play a central role in cellular metabolism producing the necessary ATP through oxidative phosphorylation. As a remnant of their prokaryotic past, mitochondria contain their own genome, which encodes 13 subunits of the oxidative phosphorylation system, as well as the tRNAs and rRNAs necessary for their translation in the organelle. Mitochondrial protein synthesis depends on the import of a vast array of nuclear-encoded proteins including the mitochondrial ribosome protein components, translation factors, aminoacyl-tRNA synthetases or assembly factors among others. Cryo-EM studies have improved our understanding of the composition of the mitochondrial ribosome and the factors required for mitochondrial protein synthesis and the advances in next-generation sequencing techniques have allowed for the identification of a growing number of genes involved in mitochondrial pathologies with a defective translation. These disorders are often multisystemic, affecting those tissues with a higher energy demand, and often present with neurodegenerative phenotypes. In this article, we review the known proteins required for mitochondrial translation, the disorders that derive from a defective mitochondrial protein synthesis and the animal models that have been established for their study.